Pengembangan Booklet pada Materi Merangkum Buku Fiksi Kelas VII SMP Negeri 2 Gunungsitoli Utara - Yudika Rahmawani Zebua; Riana; Lestari Waruwu (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this study is to determine the development of Booklets on material summarizing fiction books grade VII SMP Negeri 2 North Gunungsitoli. This type of research is development (Research and Development). The development model used is the Hannafin and Peck model which consists of four phases namely needs analysis, design, development and implementation and Evaluation and Revision. This Booklet product was developed through a validity test stage by three validators (material experts, linguists, and design experts), small group tests, and large group trials. The results of data analysis, Booklet products on the material summarizing class VII fiction books have been tested valid and feasible by material expert validators in revision III 100%, linguist validators in revision II 94.2%, and design expert validators in revision II 98.4%. The practicality of Booklet in small group trials was 97.2%, and large group trials were 96.9% with very practical categories. Booklet's effectiveness has also been shown to be highly effective with an average hearing for small group trials of 84.3% and large group trials of 96.5%. Based on the results of the research above, the Booklet in the material summarizes the fiction book grade VII SMP Negeri 2 Gunungsitoli Utara which has been developed with the Hannafin and Peck model has met the requirements and is suitable for use